Attitude Contribution Students on Professional to the Student Dicipline S1 Primary School Education Open University at Study Groups Barabai - Siti Aisyah (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2017)
Attitude is a factor in man which can encourage or lead to certain behaviors. Aimed this study to analyze the students 'attitude about the picture on the profession, description of students discipline and know how big contribution to the students' attitude towards discipline student profession S1 Primary Education Open University Study Group (UT PGSD POKJAR) Barabai. The sample used 60 students. Data was collected using a questionnaire form questioner, which is given to all students. The results of descriptive statistical analysis showed that the attitude of students to the profession belong in either category, the discipline of students classified in the high category. Based on the analysis simple regression test results of the analysis obtained contributions X1 - Y = 40.2%, while the significance of the contribution of students to the profession attitude towards discipline students obtained the result t = 13.12, chances of error of 0.000. Keywords: students attitude in profession, student discipline